The adolescent athlete's heart; A miniature adult or grown-up child? - Pieles, G. E.; Stuart, A. G. (Clinical Cardiology, 2020)
The systematic development of early age talent in sports academies has led to the professionalization of pediatric sport and the sports physician need to be aware of pediatric cardiological problems. Research into the medical cardiac care and assessment of the pediatric athlete are accumulating, but specific pediatric international guidelines are not available yet and reference data for ECG and echocardiography are incomplete, in particular for the age group <12 years of age. This article is an introduction to the physiological and diagnostics specifics of the pediatric athlete. The focus lies in the differences in presentation and diagnosis between pediatric and adult athletes for the most common pathologies. Reference data for electrical and structural adaptations to intensive exercise are sparse particularly in athletes aged below 12 years old. Training related changes include decrease of resting heart rate, increase of cardiac output, ventricular cavity size, and wall thickness. Cardiac hypertrophy is less pronounced in pediatric athletes, as HR mediated cardiac output increase to endurance exercise is the dominant mechanism in peripubertal children. As in adults, the most pronounced cardiovascular adaptations appear in classical endurance sports like rowing, triathlon, and swimming, but the specifics of pediatric ECG and echocardiographic changes need to be considered.